Nobiletin and its derivatives overcome multidrug resistance (MDR) in cancer: total synthesis and discovery of potent MDR reversal agents - Senling Feng; Huifang Zhou; Deyan Wu; Dechong Zheng; Biao Qu; Ruiming Liu; Chen Zhang; Zhe Li; Ying Xie; Hai-Bin Luo (Elsevier, 2020)
Our recent studies demonstrated that the natural product nobiletin (NOB) served as a promising multidrug resistance (MDR) reversal agent and improved the effectiveness of cancer chemotherapy in vitro. However, low aqueous solubility and difficulty in total synthesis limited its application as a therapeutic agent. To tackle these challenges, NOB was synthesized in a high yield by a concise route of six steps and fourteen derivatives were synthesized with remarkable solubility and efficacy. All the compounds showed improved sensitivity to paclitaxel (PTX) in P-glycoprotein (P-gp) overexpressing MDR cancer cells. Among them, compound 29d exhibited water solubility 280-fold higher than NOB. A drug-resistance A549/T xenograft model showed that 29d, at a dose of 50 mg/kg co-administered with PTX (15 mg/kg), inhibited tumor growth more effective than NOB and remarkably increased PTX concentration in the tumors via P-gp inhibition. Moreover, Western blot experiments revealed that 29d inhibited expression of NRF2, phosphorylated ERK and AKT in MDR cancer cells, thus implying 29d of multiple mechanisms to reverse MDR in lung cancer. Key words: Nobiletin, Cancer multidrug resistance, Mechanism, Nobiletin, P-gp inhibition, Reversal agents, Solubility, Total synthesis